THE EFFECT OF STOCK RETURNS, TRADING VOLUME, AND STOCK PRICE VOLATILITY ON THE BID-ASK SPREAD - Marcelitha Riskyla; Dewa Gede Wirama (Adisam Publisher, 2025)
Stocks are the most popular investment instruments in the capital market. Investors use various types of information in their investment activities to gain maximum profit. One such piece of information is the bid-ask spread. Trading activities on the Indonesia Stock Exchange are inseparable from the movement of the distance between the bid and ask (offer), yet in general, investors tend to pay little attention to the stock bid-ask spread. Therefore, this study aims to analyze the effect of stock returns, stock trading volume, and stock price volatility on the bid-ask spread. This research was conducted on companies listed on the Indonesia Stock Exchange for the 2018–2022 period by accessing data through the official website of the Indonesia Stock Exchange (IDX). This is a quantitative study with a sample of 274 companies using probability sampling with the proportionated stratified random sampling technique. The analysis method used is multiple linear regression. The results of this study show that stock returns have a significant positive effect on the bid-ask spread, stock trading volume has a significant positive effect on the bid-ask spread, and stock price volatility also has a significant positive effect on the bid-ask spread in companies listed on the Indonesia Stock Exchange during the 2018–2022 period. This study can serve as a benchmark for determining which company stocks to invest in by analyzing variables supported by signaling theory and capital market theory, in which a liquid or efficient capital market encourages investors to participate in investment activities.